Water and forage intake, diet digestibility, and blood parameters of beef cows and heifers consuming water with varying concentrations of total dissolved salts. (7th October 2021) - Moehlenpah, Alexandra N; Ribeiro, Luana P S; Puchala, Ryszard; Goetsch, Arthur Louis; Beck, Paul; Pezeshki, Adel; Gross, Megan A; Holder, Amanda L; Lalman, David L
Abstract: The objective of this study was to investigate the effects of water quality on water intake (WI ), forage intake, diet digestibility, and blood constituents in beef cows and growing beef heifers. This was a replicated 5 × 5 Latin square with five drinking water treatments within each square: 1) fresh water (Control); 2) brackish water (100 BRW treatment) with approximately 6, 000 mg/kg total dissolved solids (TDS ); 3) same TDS level as 100 BRW achieved by addition of NaCl to fresh water (100 SLW); 4) 50% brackish water and 50% fresh water to achieve approximately 3, 000 mg/kg TDS (50 BRW); and 5) same TDS level as 50 BRW achieved by addition of NaCl to fresh water (50 SLW). Each of the five 21-d periods consisted of 14 d of adaptation and 5 d of data collection. Animals were housed individually and fed mixed alfalfa ( Medicago sativa ) grass hay cubes. Feed and WI were recorded daily. Data were analyzed with animal as the experimental unit. Age, treatment, and age × treatment were fixed effects, and animal ID within age was the random variable for intake, digestibility, and blood parameter data. Water and feed intake were greater than expected, regardless of age or water treatment. No treatment × age interactions were identified for WI ( P = 0.71), WI expressed as g/kg body weight (BW ; P = 0.70), or dry matter intake (DMI ; P = 0.21). However, there was an age × treatment tendency for DMI when scaled to BW ( P = 0.09) in cows consuming 100 BRW compared with fresh water. No differences were found for the other three treatments. Heifers provided 50 SLW water consumed less ( P < 0.05) feed (g/kg BW) compared with heifers provided fresh water and 100 BRW. No differences ( P > 0.05) in water, DMI, feed intake, or diet digestibility were found due to water quality treatment. In conclusion, under these conditions, neither absolute WI, absolute DMI, nor diet digestibility was influenced by the natural brackish or saline water used in this experiment. These results suggest that further research is necessary to determine thresholds for TDS or salinity concentration resulting in reduced water and/or feed intake and diet digestibility.